Heparanase expression in Langerhans cell histiocytosis. Issue 10 (15th April 2014) - Dvir, Rina; Vlodavsky, Israel; Ilan, Neta; Bitan, Menachem; Issacov, Josephine; Elhasid, Ronit
<x xml:space="preserve">Abstract</x> Heparanase is an endo‐beta D‐glucuronidase capable of cleaving heparan sulfate side chains, yielding heparan sulfate fragments. Heparanase activity has been correlated with the metastatic potential of tumor‐derived cells, angiogenesis, autoimmunity and inflammation. We performed a study of heparanase expression in specimens obtained from patients with Langerhans cell histiocytosis (LCH). Paraffin embedded slides from 25 patients were studied by immunohistochemistry for heparanase. Most patients had positive staining for heparanase (21/25). There was no positive association with severity of disease and other clinical characteristics. Further studies are required to clarify the role of heparanase in the pathogenesis of LCH. Pediatr Blood Cancer 2014; 61:1883–1885. © 2014 Wiley Periodicals, Inc.